The Rapidly Evolving Landscape of First-Line Targeted Therapy in Metastatic Urothelial Cancer: A Systematic Review. (11th June 2021) - Lavoie, Jean-Michel; Sridhar, Srikala S.; Ong, Michael; North, Scott; Alimohamed, Nimira; McLeod, Deanna; Eigl, Bernhard J.
Abstract : Background: Metastatic urothelial carcinoma (mUC) historically is treated with first-line platinum-based combination chemotherapy, preferably cisplatin plus gemcitabine whenever possible. In recent years, multiple classes of targeted therapy have demonstrated benefit, with some receiving approval in mUC. This review will summarize phase III efficacy and safety data for targeted agents, principally immune checkpoint inhibitors (ICIs), as either first-line or first-line switch-maintenance therapy for mUC and interpret these findings in the context of the current treatment landscape. Materials and Methods: Published and presented phase III data on targeted therapy for the first-line or first-line switch-maintenance treatment of mUC were identified using the key search terms "targeted therapy" AND "urothelial carcinoma" AND "advanced" OR respective aliases according to the guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: Of the six eligible phase III targeted therapy trials, two assessing ICIs met their primary endpoints in platinum-eligible patients. First-line ICI plus chemotherapy combinations have not improved overall survival (OS), although final OS results of the IMVigor 130 trial are pending. Switch-maintenance using an ICI in patients achieving at least stable disease following platinum-based chemotherapy statistically significantly improved OS (21.4 vs. 14.3 months, hazard ratio, 0.69; 95% confidence interval, 0.56–0.86; p = .001). Current sequencing options for mUC include first-line platinum-based chemotherapy with a switch to ICI either immediately or upon disease progression. Conclusion: Recent targeted therapy trials have expanded ICI sequencing options for mUC. The treatment landscape is likely to evolve rapidly, with results from multiple phase III trials expected in the next 5 years. Implications for Practice: Multiple classes of targeted agents are approved for use in metastatic urothelial carcinoma (mUC). Six phase III trials have recently provided insight on the benefit of these agents in the first-line setting. In platinum-eligible patients, immune checkpoint inhibitors (ICIs) combined with first-line platinum-based chemotherapy failed to demonstrate improved survival, although ICI monotherapy as switch-maintenance significantly improved overall survival in patients with mUC who had achieved at least stable disease following first-line platinum-based chemotherapy. In patients ineligible for any chemotherapy, pembrolizumab, atezolizumab, or pembrolizumab in combination with enfortumab vedotin may be options. Abstract : Treatment options for metastatic urothelial carcinoma are evolving, with multiple targeted treatment options, including immune checkpoint inhibitors, showing benefit. It is unclear whether any of these agents will replace the long established first-line standard of care, platinum-based chemotherapy. This review summarizes efficacy and safety data from first-line trials and considers these findings within the current treatment landscape to offer guidance on treatment selection and sequencing.